Space Regaining Made Easy: The Case of a Severely Infraoccluded Primary Molar - Daniele Garcovich; Riccardo Aiuto; Milagros Adobes Martin (Case Reports in Dentistry)
Infraocclusion of deciduous molars is a quite common but challenging clinical situation that a paediatric dentist has to face in his everyday practice. This anomaly can lead to space loss, eruption disturbances of the permanent successor, and deformation of the occlusal plane. A case of a severely infraoccluded primary molar is presented. The treatment was carried out using a compressed NiTi wire applied only to the adjacent teeth. In three months, the space was recovered, and the infraoccluded temporary molar was extracted. After one year, the permanent successor erupted without any complication. The technique presented can be considered minimally invasive, and it involves cost- and time-efficient mechanics.